2020
DOI: 10.1177/2158244020922889
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Evaluation of Talent Training Mode of Engineering Specialty Based on Excellence Engineer Program

Abstract: Engineering talent training quality is important for the development of engineering education in China, and the excellence engineer program is an important measure for talent training, and the reform of engineering specialty can be also carried out depending on it; therefore, the construction and evaluation of talent training mode of engineering specialty based on excellent engineer program are studied in this research. First, relevant studies in engineering education are analyzed. Second, the engineering educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…An excellent engineer program is an important approach to training practical talents, which aims to change the talent-training mode of engineering education and create a new talent training mechanism through school-enterprise cooperation. The Excellence engineer program is one of the methods to promote the quality of engineering education in China, which can form a novel talent education process with stable teaching contents, curriculum system, management system, and evaluation method based on modern educational theory" [18].…”
Section: Resultsmentioning
confidence: 99%
“…An excellent engineer program is an important approach to training practical talents, which aims to change the talent-training mode of engineering education and create a new talent training mechanism through school-enterprise cooperation. The Excellence engineer program is one of the methods to promote the quality of engineering education in China, which can form a novel talent education process with stable teaching contents, curriculum system, management system, and evaluation method based on modern educational theory" [18].…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of the weight values of the three second-level indicators corresponding to Input evaluation were B4 (0.476) > B5 (0.267) > B6 (0.258); the teacher input had the highest weight, while practice and training had the lowest weight. It is imperative to optimize the faculty in order to improve practice teaching; this improves both disciplinary coverage and the smooth operation of the proposed practice teaching system (Zhao et al, 2020). Teachers need customized training to improve specific skills or to acquire new ones.…”
Section: Discussionmentioning
confidence: 99%
“…There are 18 new undergraduate universities in China that have participated in the conformity assessment, 305 majors have qualified for the professional certification for engineering education, 262 have qualified for the professional certification for teacher training, and 269 have qualified for the professional certification for medicine (Ministry of Education of the People's Republic of China, 2021a). It is considered to improve the quality of China's engineering talent cultivation (Zhao et al, 2020). Therefore, it is evident that undergraduate education presently places great emphasis on evaluating university majors and undergraduate education (Zhang & Guo, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the current two-wheel driving background of new concepts and new technologies, the traditional engineering thinking teaching system of surveying and mapping engineering faces four major contradictions, which is difficult to meet the new requirements of innovative talents cultivation. Based on undertaking 7 provincial and ministerial level and 3 university and bureau level educational reform pro-jects, this paper designs a multi-level training system of "thinking transformation -professional development -model change", and carries out reform and practice from multiple links of "curriculum system -textbook construction -practical teaching -innovation credit", and proposes a talent training system based on the integrated thinking mode of engineering and research [10][11][12][13][14][15][16] , as shown in Figure 1. It can be seen from Figure 1 that the overall design of the talent training system based on the integrated thinking mode of engineering and research mainly includes three levels: first, the talent thinking is changed from single engineering thinking to integrated thinking of engineering and research to realize the thinking transformation; Secondly, the direction of intelligent navigation has been expanded from traditional surveying and mapping engineering to surveying and mapping engineering (intelligent navigation experimental class), and the extension construction of surveying and mapping specialty has been expanded; The last is the innovation of training system.…”
Section: Thoughts On the Construction Of The Integrated Thinking Mode...mentioning
confidence: 99%